Where do Energy-Poor Households Live? Empirical Evidence from Indonesia - Hasibuan, Dewi Yuliandini; Nasrudin, Rus'an (Universitas Negeri Semarang, 2022)
Empirical analysis on the links between geography and energy access in archipelago setting is still limited. In particular, the territorial identification of energy poverty in Indonesia is still missing. Our study maps geographical location and estimates factors that determines the probability of being energy poor household in relation to electricity. We used the OLS (Ordinary Least Square) estimation and utilized the socioeconomic survey (Susenas) combined with data on terrain elevation, presence of geographic features such as mountainside, topography characteristics, ocean and forest obtained from the village census (PODES). The results show that energy poverty in Eastern part of Indonesia is larger than in the Western. In Eastern Indonesia, we estimate that 13.5% of the total households are energy poor compared to the Western which only 7.21%. Households located in the forest area was the dominant factor to influence prevalence of energy poverty among geographic constraints, with magnitude of influence at 22-23 percentage point to non-forest residents. Secondly, the presence of steep-sloped terrain is the next meaningful geographical constraint with contribution effect to energy poverty prevalence at around 18 percentage point. The result highlighted priority of locations in which resource and policy to reduce energy deprivation need to be allocated.